Some Adipocytokines (Leptin, Resistin, Vesfatin) Relationships with Obesity (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Adipose tissue is widely concerned as an active endocrine organ, and have a crucial role in the   innate immune system . Adipocytokines perform a role in the pathogenesis of insulin resistance and related metabolic complications, and also they cause both beneficial and detrimental immune and inflammatory effects. And most of these adipocytokines are physiologically important for metabolism, such as leptin, resistin, and visfatin which may serve as a missing connection between obesity and diabetes in the causal relation. Also it may  have myriad anti-inflammatory effect. It should be considered the functional balance of the adipokines and obesity.